Functional Characterization of the Lactolisterin BU Gene Cluster of Lactococcus lactis subsp. lactis BGBU1-4 - Miljkovic, Marija; Lozo, Jelena; Mirkovic, Nemanja; O’Connor, Paula M.; Malesevic, Milka; Jovcic, Branko; Cotter, Paul D.; Kojic, Milan (Frontiers in Microbiology, 2018)
The gene cluster responsible for the production of the aureocin A53-like bacteriocin, lactolisterin BU, is located on plasmid pBU6 in Lactococcus lactis subsp. lactis BGBU1-4. Heterologous expression of pBU6 confirmed that production and limited immunity to lactolisterin BU were provided by the plasmid. Comparative analysis of aureocin A53-like operons revealed that the structural genes shared a low level of identity, while other genes were without homology, indicating a different origin. Subcloning and expression of genes located downstream of the structural gene, lliBU, revealed that the lactolisterin BU cluster consists of four genes: the structural gene lliBU, the abcT gene encoding an ABC transporter, the accL gene encoding an accessory protein and the immL gene which provides limited immunity to lactolisterin BU. Reverse transcription analysis revealed that all genes were transcribed as one polycistronic mRNA. Attempts to split the lactolisterin BU operon, even when both parts were under control of the PlliBU promoter, were unsuccessful indicating that expression of lactolisterin BU is probably precisely regulated at the translational level by translational coupling and is possible only when all genes of the operon are in cis constellation. Two -independent transcription terminators were detected in the lactolisterin BU operon: the first in the intergenic region of the lliBU and abcT genes and the second at the end of operon. Deletion of the second transcription terminator did not influence production of the bacteriocin in lactococci.